Periods of the children’s life: methodical recommendations for the students of IIІ course of the medical faculty - Bugaevska, M. O.; Zimnytska, T. V.; Бугаєвська, Мар’яна Олександрівна; Зімницька, Тетяна Василівна (Kharkiv : V. N. Karazin Kharkiv National University, 2018)
Methodical recommendations are devoted to the development of a child from the moment of conception to the age of 18. A detailed description of each period of intrauterine and extrauterine life is provided. The pathological conditions of the child in different age periods are described. Methodical recommendations are worked out on the basis of the Program of discipline of «Propedeutics of pediatrics» for students of higher medical educational institutions of III–IV levels of accreditation, authorized by Ministry of Health of Ukraine. These recommendations are intended for the 3th years English-speaking medical students.

Методичні рекомендації присвячені розвитку дитини з момента запліднення до 18 років. Надано детальну характеристику кожного періода внутрішньоутробного та позаутробного життя. Описано патологічнв стани дитини в різні вікові періоди. Методичні рекомендації розроблено на основі програми дисципліни «Пропедевтика педіатрії» для студентів вищих медичних навчальних закладів III–IV рівнів акредитації, затвердженої МОЗ України. Методичні рекомендації призначено для англомовних студентів 3 курсу медичного факультету.
Періоди дитячого віку : методичні рекомендації для студентів IIІ курсу медичного факультету
Навчальне видання
Keywords: MEDICINE::Internal medicine::Paediatric medicine; SOCIAL SCIENCES; embryonic period; fetal period; newborn; infant period; school age; ембріональний період; фетальний період; новонароджений; період грудного віку; шкільний вік